2019
DOI: 10.1101/863076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacteriophages inhibit biofilms formed by multi-drug resistant bacteria isolated from septic wounds

Abstract: 7 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 88 publications
(115 reference statements)
1
3
0
Order By: Relevance
“… Sutherland et al (2004) reported that phage therapy assumed as an attractive option to prevent and control the formation of biofilm related infections Verma et al (2010) concluded that the biofilms eradication requires the combination of both antibiotics and bacteriophages, while ( Hughes et al, 1998 ) hypothesized that combining bacteriophages with DNase enzymes efficiently destroys the biofilm matrix. However, Pallavali et al (2019) demonstrated that the biofilm may be removed purely by the bacteriophage itself and deemed it a significant development in the hunt for additional agents to replace antibiotics were consistent with the findings of the current investigation. Biofilm makes it difficult for traditional antibiotics to penetrate the cells making them less responsive to antibiotics ( Mittal et al, 2015 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“… Sutherland et al (2004) reported that phage therapy assumed as an attractive option to prevent and control the formation of biofilm related infections Verma et al (2010) concluded that the biofilms eradication requires the combination of both antibiotics and bacteriophages, while ( Hughes et al, 1998 ) hypothesized that combining bacteriophages with DNase enzymes efficiently destroys the biofilm matrix. However, Pallavali et al (2019) demonstrated that the biofilm may be removed purely by the bacteriophage itself and deemed it a significant development in the hunt for additional agents to replace antibiotics were consistent with the findings of the current investigation. Biofilm makes it difficult for traditional antibiotics to penetrate the cells making them less responsive to antibiotics ( Mittal et al, 2015 ).…”
Section: Discussionsupporting
confidence: 85%
“…These findings were consistent with ( Salim et al, 2013 ). Pallavali et al (2019) suggested that decrease in weight gain due to oxidative stress caused by colibacillosis. Of interest we found that a higher bacteriophage dose and intra-tracheal inoculation lead to significantly decrease shedding of E. coli in lung tissue comparing with infected non treated group ( Tawakol et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phages isolated against K. pneumoniae were also tested for their ability to inhibit and eradicate biofilm production in vitro as previously described. 27 Briefly, freshly grown bacterial culture at OD 600 = 0.5 diluted with L.B broth at factor 10:100 was added to the first column of 96 well micro-titer plates followed by 100 µL of phage suspension at MOI of 0.01 to each well of the first column. 28 The plates were incubated for 8 hours at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…In addition are combination physiochemical and biological approaches using stains that indicate bacterial viability such as resazurin [ 117 , 118 ] and soluble tetrazolium dyes [ 110 , 119 , 120 , 121 ]. Especially crystal violet staining is used in determining the phage impact on bacterial biofilms, particularly in 96-well microtiter plate formats [ 108 , 122 , 123 , 124 ]. This allows total biofilm biomass quantification [ 125 , 126 ].…”
Section: Improving Phage-biofilm In Vitro Experimentationmentioning
confidence: 99%